Eksistensi Tari Andun Dalam Upacara Adat Perkawinan Di Kecamatan Seluma Kabupaten Seluma Provinsi Bengkulu - Windi Kartika Surya; Nerosti Nerosti (SENDRATASIK UNP, 2021)
This research has a problem regarding the formulation of "The Existence of Andun Dance in Seluma Marriage, Seluma Regency, Bengkulu Province". The purpose of this research is to describe and analyze the existence of Andun Dance in traditional wedding ceremonies in Seluma District, Seluma Regency, Bengkulu Province. This research uses descriptive qualitative analysis. Data collection techniques or through literature study, observation, interviews and documentation. The research found that the Andun Dance consists of two types, namely: (1) the Andun lelawanan dance which is danced in pairs and women by bachelors; (2) and most of the Andun Dance by many dancers have been married. Andun dancers are mostly men and women performing separately. There is a periodization of Andun dance through 2 periods, namely: (1) periodization of 2003-2015, Andun Lelawanan Dance exists more than most Andun Dances, according to the purpose of the dance presented is to seek love; (2) Periodically from 2015 to present, Andun Dance is the most widely available. In 2019, the choreography in the Andun Dance was developed which was contested. Dancers in costume from the perspective of the Andun Dance competition, where the female dancers use modern borkat kebaya, songket cloth as a skirt, and a scarf. While the clothes are boy dancer/koko, coat, trousers, gloves, and a skullcap.